1985
DOI: 10.1002/art.1780280709
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle dysfunction and unexplained dyspnea in systemic lupus erythematosus

Abstract: The role of inspiratory muscle dysfunction in lung volume restriction and unexplained dyspnea was studied in 16 consecutive patients with systemic lupus erythematosus. Maximal mouth inspiratory pressure PI^) and maximal transdiaphragmatic pressure (Pdi max) were measured. Pdi and its components were determined during quiet breathing. No significant associatiam was found between the activity of the disease, several serologic markers, and the inspiratory muscle dysfunction. No specific anti-skeletal muscle antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Because pathologic data are unavailable, theories of its etiology are speculative. In the past, it has been attributed successively to a surfactant deficiency, [15,43] isolated diaphragmatic myopathy, [34,39,44,53,65,67] phrenic nerve dysfunction, [45,66] chest wall dysfunction, [19,71] and pleural adhesions, [31,39] but none of these hypotheses has been unequivocally confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Because pathologic data are unavailable, theories of its etiology are speculative. In the past, it has been attributed successively to a surfactant deficiency, [15,43] isolated diaphragmatic myopathy, [34,39,44,53,65,67] phrenic nerve dysfunction, [45,66] chest wall dysfunction, [19,71] and pleural adhesions, [31,39] but none of these hypotheses has been unequivocally confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction in chest wall expansion, which has been suspected in shrinking lung syndrome of SLE,6 could modify the activity of rib cage muscle mechanoreceptors. 9 An early pulmonary interstitial involvement, which has been reported in multisystem disorders,1 may increase pulmonary vagal receptor af¬ ferent information.…”
Section: Breathing Patternmentioning
confidence: 99%
“…are extremely scarce in SLE. 6,9 In patients with decreased respiratory muscle force, Jacobelli et al9 showed that light exercise resulted in increased venti¬ lation, mostly sustained by increase in respiratory fre¬ quency (Rf), with modest changes in tidal volume (Vt). Incomplete respiratory muscle activation during max¬ imal voluntary efforts and a shallow pattern of breath¬ ing during maximal voluntary ventilation have recently been reported in SLE with shrinking lung syndrome.6…”
mentioning
confidence: 99%
“…Most authors agree that there would exist a dysfunction of the respiratory muscles; Jacobelli et al (7) found involvement in the inspiratory muscles in 56% of the patients.…”
Section: Discussionmentioning
confidence: 99%